Performing single phase pulsating AC controller with DIAC as driver - Gomesh Nair, Shasidharan (Universiti Malaysia Perlis, 2009)
A Single Phase Pulsating AC Controller with DIAC as Driver is actually an AC voltage controller which is also a converter which controls the voltage, current, and average power delivered to an AC load from an AC source. Electronic switches connect and disconnect the source and the load at regular intervals. In a switching scheme called phase control, switching takes place during every cycle of the source, in effect removing some of the source waveform before it reaches the load. To imply this circuit, some problems will arise such as to convert AC sources to DC source which used bridge rectifier will produce ripple waveform. It can be solve by using a RC filter or another suitable filters and regulator to regulate the voltage, so that the output becomes smooth. The load and the source current and voltage in AC voltage controller circuits may contain significant harmonics. In this Project, The harmonics content with and without the AC controller that is connected to resistive and inductive loads will be compared. The results must show that the existence of AC controller circuit will increase the harmonic on the circuit.